In Situ Activation of the Quorum-Sensing Transcription Factor TraR by Cognate and Noncognate Acyl-Homoserine Lactone Ligands: Kinetics and Consequences - Luo, Zhao-Qing (American Society for Microbiology, 2003)
Conjugal transfer of Ti plasmids of Agrobacterium tumefaciens is controlled by a quorum-sensing system composed of the transcriptional activator TraR and its acyl-homoserine lactone quormone N-(3-oxo-octanoyl)-l-homoserine lactone (3-oxo-C8-HSL). The population density dependence of quorum-sensing systems can often be circumvented by addition of the quormone to cultures at low cell numbers. However, the quorum-dependent activation of Ti plasmid conjugal transfer exhibited a lag of almost 8 h when the quormone was added to donor cells at low population densities (Piper and Farrand, J. Bacteriol. 182:1080-1088, 2000). As measured by activation of a TraR-dependent traG::lacZ reporter fusion, TraR in cells exposed to the cognate signal for 5 min showed detectable activity, while exposure for 15 min resulted in full activity. Thus, the lag in activation is not due to some intrinsic property of TraR. Cells exposed to the agonistic analog N-(3-oxo-hexanoyl)-l-homoserine lactone (3-oxo-C6-HSL) exhibited similar induction kinetics. However, activation of the reporter in cells exposed to the poorly effective alkanoyl acyl-HSL N-hexanoyl-l-homoserine lactone (C6-HSL) required the continued presence of the signal. As measured by an in vivo repressor assay, TraR activated by 3-oxo-C6-HSL or by 3-oxo-C8-HSL remained active for as long as 8 h after removal of exogenous signal. However, TraR activated by the alkanoyl quormone C6-HSL rapidly lost activity following removal of the signal. In quormone retention assays, which measure signal binding by TraR, cells grown with either of the two 3-oxo-acyl-HSL quormones retained the ligand after washing, while cells grown with C6-HSL lost the alkanoyl-HSL concomitant with the rapid loss of TraR activity. We conclude that TraR rapidly binds its quormone and that, once bound, the cognate signal and its close homologs are tightly retained. Moreover, in the absence of other regulatory factors, activated TraR remains functional after removal of the signal. On the other hand, poorly active signals are not tightly bound, and their removal by washing leads to rapid loss of TraR activity.